Identification and analysis of low-molecular-weight dissolved organic carbon in subglacial basal ice ecosystems by ion chromatography - O'Donnell, Emily C.; Wadham, Jemma L.; Lis, Grzegorz P.; Tranter, Martyn; Pickard, Amy E.; Stibal, Marek; Dewsbury, Paul; Fitzsimons, Sean (European Geosciences Union, 2016)
Determining the concentration and composition of dissolved organic carbon (DOC) in glacial ecosystems is important for assessments of in situ microbial activity and contributions to wider biogeochemical cycles. Nonetheless, there is limited knowledge of the abundance and character of DOC in basal ice and the subglacial environment and a lack of quantitative data on low-molecular-weight (LMW) DOC components, which are believed to be highly bioavailable to microorganisms. We investigated the abundance and composition of DOC in basal ice via a molecular-level DOC analysis. Spectrofluorometry and a novel ion chromatographic method, which has been little utilized in glacial science for LMW-DOC determinations, were employed to identify and quantify the major LMW fractions (free amino acids, carbohydrates, and carboxylic acids) in basal ice from four glaciers, each with a different type of overridden material (i.e. the pre-entrainment sedimentary type such as lacustrine material or palaeosols). Basal ice from Joyce Glacier (Antarctica) was unique in that 98% of the LMW-DOC was derived from the extremely diverse free amino acid (FAA) pool, comprising 14 FAAs. LMW-DOC concentrations in basal ice were dependent on the bioavailability of the overridden organic carbon (OC), which in turn was influenced by the type of overridden material. Mean LMW-DOC concentrations in basal ice from Russell Glacier (Greenland), Finsterwalderbreen (Svalbard), and Engabreen (Norway) were low (0–417nMC), attributed to the relatively refractory nature of the OC in the overridden palaeosols and bedrock. In contrast, mean LMW-DOC concentrations were an order of magnitude higher (4430nMC) in basal ice from Joyce Glacier, a reflection of the high bioavailability of the overridden lacustrine material (> 17% of the sediment OC comprised extractable carbohydrates, a proxy for bioavailable OC). We find that the overridden material may act as a direct (via abiotic leaching) and indirect (via microbial cycling) source of DOC to the subglacial environment and provides a range of LMW-DOC compounds that may stimulate microbial activity in wet subglacial sediments.